Limiting factors in capercaillie (Tetrao urogallus) conservation - Moreira Boman, Christer; Pettersson, Andreas (2021)
With current extinction rates comparable with the rates of previous mass extinctions and humanities necessity of biodiversity, conservation of habitat and species should be regarded as paramount whenever planning land use. In this paper we have focused on the Western capercaillie (Tetrao urogallus) an umbrella species in Eurasian boreal and temperate forests. Capercaillie numbers have been reduced in mainland Europe and British Isles during the last century mainly due to increased predator populations, habitat loss, fragmentation and degradation as a result of human development of agriculture and land use change. Human recreation in sites with capercaillie show increased levels of stress in the capercaillies which might contribute to their decline. Programs in Scotland, Germany, Spain and Poland have the aim to aid or reintroduce populations in the capercaillies historic range. Practices with the aims to reintroduce or re-stock populations often consist of releasing individuals reared in facilities or breeding centers into suitable habitat. High mortality shortly after releasing due to high predation as a result of mal adapted physical and behavior traits leads to failure in most programs. Predator management and new techniques that improve the physical and behavioral quality in reared capercaillies such as choice of rearing method, large flight pens, elevated roost and anti-predatory training have shown increased fitness and increased survival. The use of PVA tools is effective when comparing different procedures or scenarios and should be used as a decision basis.